Produced by Irving Thalberg : theory of studio-era filmmaking - Salzberg, Ana (Edinburgh University Press, 2020)
Drawing on archival sources, this is the first book to explore Thalberg's insights into casting, editing, story composition and the importance of the mass audience from a theoretical perspective.
Keywords: Thalberg, Irving G., -- 1899-1936.; Thalberg, Irving G., -- 1899-1936; Motion picture producers and directors -- United States -- Biography.; Motion picture industry -- United States -- History.; Producteurs et réalisateurs de cinéma -- États-Unis -- Biographies.; Cinéma -- Industrie -- États-Unis -- Histoire.; PERFORMING ARTS -- Film & Video -- Direction & Production.; Motion picture industry; Motion picture producers and directors; United States; Biography; Biographies; History; Biographies.